Preparation method of AuAg alloy cluster / g-C3N4 photocatalyst

By preparing AuAg alloy clusters/g-C3N4 photocatalysts, the heterostructure is formed by using the synergistic effect of AuAg alloy clusters and wet impregnation technology, which solves the problems of limited active sites and low efficiency of g-C3N4 photocatalysts, and achieves efficient photocatalytic water decomposition and stable catalytic performance.

CN119680600APending Publication Date: 2025-03-25NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411636486.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride (g-C3N4) photocatalysts have limited active sites and high photogenerated electron recombination efficiency during photocatalytic water decomposition, resulting in low efficiency.

Method used

By preparing AuAg alloy clusters/g-C3N4 photocatalysts, the catalytic activity is synergistically improved by electron transfer and interaction of AuAg alloy clusters, and AuxAg25-x NCs are loaded onto CN through wet impregnation technology to form heterostructures to improve photocatalytic performance.

Benefits of technology

The photocatalytic activity of the photocatalyst is significantly improved, the effective separation of the photogenerated electron-hole pair at the interface junction is enhanced, the stability of the catalyst is maintained, and the synthesis cost of precious metals is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680600A_ABST
    Figure CN119680600A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an AuAg alloy cluster / g-C3N4 photocatalyst, and belongs to the technical field of photocatalysts.The preparation method comprises the steps that a HAuCl4 aqueous solution and an AgNO3 aqueous solution are added into an MHA aqueous solution under stirring, then a H2O solution, a NaOH solution and a NaBH4 solution are sequentially added, and Au12Ag13 NCs is obtained after mixing and stirring reaction; the preparation method comprises the following steps: dissolving dicyandiamide and ammonium chloride in deionized water, drying, calcining to obtain a faint yellow solid, grinding, roasting in a protective atmosphere, and collecting solid powder CN; the preparation method comprises the following steps: uniformly dispersing CN powder in deionized water, respectively adding different volumes of Au12Ag13 NCs, stirring for reaction, and drying to obtain the AuAg alloy cluster / g-C3N4 photocatalyst. A better catalytic effect is shown. Besides, Ag is stable relative to Au, wide in source and low in cost, the production cost of the composite catalyst is saved, and due to the unique physical and chemical structure of the AuAg alloy cluster, the composite catalyst shows more excellent catalytic performance. The method disclosed by the invention is an important method for constructing the g-C3N4-based composite photocatalyst and has cost benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalysts, and in particular relates to a method for preparing an AuAg alloy cluster / g-C3N4 photocatalyst. Background Art

[0002] Hydrogen energy is a clean energy with great application prospects and is the main substitute for fossil fuels in the future. Replacing fossil fuels with hydrogen can not only reduce environmental pollution and weaken the threat of harmful gases to the global climate and residents' daily lives, but also meet the United Nations' requirements for clean energy and green development in the 21st century. The earth has abundant sunlight and water resources. Using sunlight to decompose water to produce hydrogen is an inexhaustible method. Photocatalytic hydrogen production can use sunlight to produce hydrogen on a large scale, which is a green and energy-saving process.

[0003] With the development of non-metallic catalytic materials, non-metallic semiconductor graphite carbon nitride (g-C3N4) has been favored by many scientists. g-C3N4 is a narrow bandgap semiconductor with a bandgap of about 2.7 eV. The positions of the conduction band (CB) and the valence band (VB) are conducive to the redox of water. It can withstand a high temperature of 600 °C in air and has chemical stability against acids, alkalis and organic solvents. Compared with inorganic semiconductors, the band structure of g-C3N4 is easy to adjust, the synthesis process is relatively simple and green, and it absorbs visible light well, so it is more suitable for participating in photocatalytic water splitting reactions. Although g-C3N4 has received widespread attention from scientists, the problems of limited active sites and high recombination efficiency of photogenerated electrons make it inefficient in the photocatalytic process. In general, the photocatalytic performance of g-C3N4 is mainly affected by the absorption of visible light, the surface reaction rate and the recombination rate of photogenerated carriers. At present, researchers often use six methods to improve its photocatalytic performance: element doping, copolymerization, crystal manipulation, surface engineering and single atom modification, and regulation of different dimensions.

[0004] Surface modification of noble metals (such as Pt, Au, etc.) is an effective method to improve the photocatalytic activity of g-C3N4. The noble metals loaded on the photocatalyst can act as electron transfer mediators and promote the separation of electron-hole pairs. In addition, noble metal nanoparticles can increase visible light absorption through the surface plasmon resonance (SPR) effect. Although surface modification of noble metals can significantly improve the photocatalytic activity of catalysts, the expensive synthesis precursors greatly limit the large-scale application of noble metals in catalytic reactions. In contrast, using cheap metals to partially replace noble metals to synthesize alloy metal catalysts is a feasible solution for utilizing noble metal catalysts. At present, it has been reported that non-noble metals such as Zr, Cu, and Ag react with Au to form alloy catalysts. Among them, AuAg alloy catalysts have been widely studied due to their unique mechanism of action. Recent studies have shown that in AuAg alloy catalysts, gold and silver metals can complement each other through electron transfer and interaction between the two to enhance their catalytic activity. For example, in the photocatalytic water splitting process, Au can act as an electron acceptor, while Ag can promote the oxygen reduction (ORR) process. The photocatalytic water splitting process can be effectively enhanced through the synergistic effect of AuAg alloy. Currently, the AuAg alloy catalyst structures that are widely studied include: AuAg alloy nanocrystals, AuAg alloy nanoparticles, AuAg alloy nanowires, and AuAg alloy nanoclusters.

[0005] In recent years, noble metal nanoclusters have been shown to be a new type of photosensitizer. Noble metal nanoclusters are generally composed of a few or hundreds of atoms, and their size (<2 nm) is comparable to the electron Fermi wavelength, which can improve the photocatalytic activity of combined semiconductors. Atomic-precise metal clusters with precise molecular formulas, molecular purity and overall structures have rapidly developed and become star members of nanomaterials due to their unique physical and chemical properties. Metal clusters in quantum-sized states have discrete electronic energy levels and exhibit non-metallic or exciton behaviors, which are completely different from larger metallic nanoparticles that exhibit obvious surface plasmon resonances. Compared with plasmonic metal nanoparticles, cluster-based heterogeneous catalysts have shown new catalytic properties in many chemical reactions. Therefore, noble metal nanoclusters are more suitable for catalytic reactions than other nanostructured noble metal catalysts due to their unique physical and chemical properties. In addition, noble metal nanoclusters require less noble metal precursors during the synthesis process, which greatly reduces the synthesis cost in practical application processes and is an economically efficient noble metal catalyst.

[0006] The high carrier recombination rate and poor conductivity of graphite-phase carbon nitride limit its application. However, due to the quantum size effect, noble metal nanoclusters will expose more active sites when combined with semiconductor materials, thereby improving the photocatalytic performance. Summary of the invention

[0007] In order to solve the above technical problems, the present invention discloses a method for preparing AuAg alloy cluster / g-C3N4 photocatalyst, and the specific technical scheme is as follows.

[0008] A method for preparing an AuAg alloy cluster / g-C3N4 photocatalyst comprises the following steps: Step 1: Add HAuCl4 aqueous solution and AgNO3 aqueous solution to MHA aqueous solution under stirring to form MHA-Au(I) / Ag(I) complex; Step 2: Add H2O, NaOH solution and NaBH4 solution in sequence, stir the mixed solution at room temperature to react, and collect the reddish-brown AuxAg25-x NCs; Step 3: Dissolve dicyandiamide and ammonium chloride in deionized water, then dry to obtain a white fluffy solid, and calcine to obtain a light yellow solid BCN; Step 4: Grind the BCN and place it in a protective atmosphere for secondary calcination to prepare a few layers of g-C3N4 through a thermal exfoliation process, cool it naturally to room temperature, and collect the solid powder CN for later use without grinding; Step 5: Disperse CN powder evenly in deionized water; Step 6: Add different volumes of AuAg25-x NCs respectively, stir for reaction and then dry to obtain the AuAg alloy cluster / g-C3N4 photocatalyst.

[0009] Preferably, the concentrations of the HAuCl4 aqueous solution and the AgNO3 aqueous solution in step 1 are both 20 mM. The concentration of the MHA aqueous solution is 5 mM. Preferably, the amount of the HAuCl4 aqueous solution added in step 1 is 0.24-0.44 mL, the amount of the AgNO3 aqueous solution added is 0.06-0.26 mL, and the amount of the MHA aqueous solution added is 4 mL.

[0010] Preferably, the amount of H2O added in step 2 is 4 mL, the concentration of the NaOH aqueous solution is 1 mM, the amount added is 300 µL, the concentration of the NaBH4 solution is 20 mM, the amount added is 100 µL, wherein the NaBH4 solution is prepared by dissolving 43 mgNaBH4 in 10 mL of NaOH aqueous solution (0.2 M).

[0011] Preferably, the stirring reaction time in step 2 is 3 h.

[0012] Preferably, the amount of dicyandiamide added in step 3 is 1 g, the amount of ammonium chloride added is 5 g, and the amount of H2O used is 10 mL.

[0013] Preferably, the drying in step 3 and step 6 is freeze-drying the solution in a freeze dryer.

[0014] Preferably, the calcination in step 3 is performed in a muffle furnace, and the specific parameters are: heating to 550° C. at a heating rate of 3° C. / min and maintaining for 4 hours.

[0015] Preferably, the calcination in step 4 is carried out in a tubular furnace, and the specific parameters are: heating to 600° C. at a heating rate of 3° C. / min, maintaining for 2 hours, and a nitrogen flow rate of 40 mL / min.

[0016] Preferably, the protective atmosphere in step 4 is nitrogen.

[0017] Preferably, the mass of the CN powder in step 5 is 100 mg, and the amount of H2O used is 10 mL.

[0018] Preferably, the dispersion in step 5 is carried out by ultrasonic treatment.

[0019] Preferably, the Au in step 6 x Ag 25-x The amount of NCs added was 0.254-7.62 ml, and the reaction time was 1 h.

[0020] Preferably, the optimal addition amount is: HAuCl4 (20 mM, 240 µL) and AgNO3 (20 mM, 260 µL) in step 1. x Ag 25-x The amount of NCs added was 2.54 ml.

[0021] Compared with the prior art, (1) the present invention successfully synthesized AuxAg25-xNCs protected by 6-mercaptohexanoic acid (MHA) ligands, and loaded AuxAg25-x NCs onto CN by a simple wet impregnation method to form an AuxAg25-x / CN heterostructure. AuxAg25-x NCs were highly dispersed on the CN surface, forming a large number of junctions at the NCs / semiconductor interface, and the distribution of active sites was maximized due to the high dispersion of AuxAg25-x NCs, resulting in a significant enhancement of the photocatalytic activity. This enhancement can be attributed to the appropriate band structure between the two components in the binary nanocomposite, which leads to the effective separation of photogenerated electron-hole pairs at the interface junction. The composite photocatalyst maintained good stability in the recycling test. (2) The present invention shows that, compared with single-component Au NCs, the incorporation of Ag atoms in AuAg alloy clusters and the loading amount of AuAg alloy clusters will change the band structure of the composite photocatalyst, thereby affecting the photocatalytic hydrogen production performance, which may be related to the synergistic effect of Au and Ag. (3) In the present invention, Ag is relatively widely available and cheap compared to Au, so this strategy may become one of the most cost-effective methods for constructing g-C3N4-based composite photocatalysts. (4) The present invention loads AuAg25-xNCs onto ultrathin g-C3N4 NSs by simple wet impregnation to form an AuAg25-x / CN heterostructure. The AuAg alloy clusters themselves are also prepared by a simple chemical reduction method. Since Au atoms are partially replaced by Ag atoms, the synthesis cost of precious metal catalysts is greatly saved.

[0022] (5) When the ratio of Au to Ag is 12:13, the amount of hydrogen produced by the catalyst photocatalysis is the highest, and is significantly better than that of single graphite phase carbon nitride; (6) Taking Au12Ag13 NCs as the research object, the effect of the loading amount of Au12Ag13 NCs on the hydrogen production activity of the composite sample is explored. The present invention shows that when the theoretical loading amount is 0.77 wt%, the catalyst has the highest hydrogen production activity. The method of the present invention may become one of the most cost-effective methods for constructing g-C3N4-based composite photocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope schematic diagram of Au12Ag13 / CN-3; Figure 2 TEM image of Au12Ag13 NCs and schematic diagram of particle size distribution; Figure 3 TEM image of Au12Ag13 / CN-3 and schematic diagram of the size distribution of Au12Ag13 NCs loaded on Au12Ag13 / CN-3; Figure 4Schematic diagram of the performance of photocatalytic hydrogen production of Examples 1, 2, 3, 4 and 5; Figure 5 Schematic diagram of the performance of photocatalytic hydrogen production in Examples 6 and 7; Figure 6 For Au 12 Ag 13 / CN-3 photocatalytic hydrogen production stability test chart. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings.

[0025] Example 1 Step 1: First, HAuCl4 aqueous solution (20 mM, 240 μL) and AgNO3 aqueous solution (20 mM, 260 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au12Ag13 NCs were collected.

[0026] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0027] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0028] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 2.54 mL of Au12Ag13 NCs described in step 2 to the solution described in step 5, stir for 1 h and then freeze-dry to obtain the sample Au12Ag13 / CN-3 Step 7: The Au12Ag13 / CN-3 catalyst obtained in step 6 was tested for photocatalytic decomposition of water for hydrogen production. The photocatalytic decomposition of water for hydrogen production was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0029] The Au12Ag13 / CN-3 photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in FIG. Figure 4 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au12Ag13 / CN-3 photocatalyst reached 38.86 µmol, showing excellent photocatalytic hydrogen production performance under mild reaction conditions.

[0030] Example 2 Step 1: First, HAuCl4 aqueous solution (20 mM, 240 μL) and AgNO3 aqueous solution (20 mM, 260 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au12Ag13 NCs were collected.

[0031] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0032] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0033] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 0.254 mL of Au12Ag13 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au12Ag13 / CN-1 Step 7: The Au12Ag13 / CN-1 catalyst obtained in step 6 was tested for photocatalytic water decomposition and hydrogen production. The photocatalytic water decomposition and hydrogen production test was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0034] The Au12Ag13 / CN-1 photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in FIG. Figure 4 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au12Ag13 / CN-1 photocatalyst reached 17.33 µmol.

[0035] Example 3 Step 1: First, HAuCl4 aqueous solution (20 mM, 240 μL) and AgNO3 aqueous solution (20 mM, 260 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au12Ag13 NCs were collected.

[0036] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0037] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0038] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 1.27 mL of Au12Ag13 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au12Ag13 / CN-2 Step 7: The Au12Ag13 / CN-2 catalyst obtained in step 6 was tested for photocatalytic water decomposition and hydrogen production. The photocatalytic water decomposition and hydrogen production test was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0039] The Au12Ag13 / CN-2 photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in FIG. Figure 4 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au12Ag13 / CN-2 photocatalyst reached 27.16 µmol.

[0040] Example 4 Step 1: First, HAuCl4 aqueous solution (20 mM, 240 μL) and AgNO3 aqueous solution (20 mM, 260 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au12Ag13 NCs were collected.

[0041] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace. The temperature is raised to 550 °C at a rate of 3 °C / min and maintained for 4 h. The resulting light yellow solid is named BCN.

[0042] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0043] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 7.62 mL of Au12Ag13 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au12Ag13 / CN-4 Step 7: The Au12Ag13 / CN-4 catalyst obtained in step 6 was tested for photocatalytic decomposition of water for hydrogen production. The photocatalytic decomposition of water for hydrogen production was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0044] The Au12Ag13 / CN-4 photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in the figure. Figure 4 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au12Ag13 / CN-4 photocatalyst reached 19.81 µmol.

[0045] Example 5 Step 1: First, HAuCl4 aqueous solution (20 mM, 500 μL) was added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form a complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au25 NCs were collected.

[0046] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0047] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0048] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 2.54 mL of Au25 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au25 / CN Step 7: The Au25 / CN catalyst obtained in step 6 was tested for photocatalytic decomposition of water to produce hydrogen. The photocatalytic decomposition of water to produce hydrogen was tested at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0049] The Au25 / CN photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in FIG. Figure 4 As shown in the figure, after 4 h of reaction under visible light conditions, the hydrogen production of Au25 / CN photocatalyst reached 33.31 µmol.

[0050] Example 6 Step 1: First, HAuCl4 aqueous solution (20 mM, 360 μL) and AgNO3 aqueous solution (20 mM, 140 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au18Ag7 NCs were collected.

[0051] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a crucible with a lid and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0052] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0053] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 1.27 mL of Au18Ag7 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au18Ag7 / CN Step 7: The Au18Ag7 / CN catalyst obtained in step 6 was tested for photocatalytic water decomposition and hydrogen production. The photocatalytic water decomposition and hydrogen production test was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0054] The Au18Ag7 / CN photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in FIG. Figure 5 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au18Ag7 / CN photocatalyst reached 21.43 µmol.

[0055] Example 7 Step 1: First, HAuCl4 aqueous solution (20 mM, 440 μL) and AgNO3 aqueous solution (20 mM, 60 μL) were added to MHA aqueous solution (5 mM, 4 mL) under magnetic stirring at 300 rpm to form MHA-Au(I) / Ag(I) complex; Step 2: H2O (100 μL), NaOH solution (1 M, 300 μL) and NaBH4 solution (112 mM, 100 μL) were added to the MHA-Au(I) / Ag(I) complex described in step 1 in sequence. The NaBH4 solution was prepared by dissolving 43 mg NaBH4 in 10 mL NaOH aqueous solution (0.2 M). The mixed solution was then stirred at room temperature for 3 h, and the reddish-brown Au22Ag3 NCs were collected.

[0056] Step 3: Dissolve 1 g of dicyandiamide and 5 g of ammonium chloride in 40 mL of deionized water. The solution is freeze-dried in a freeze dryer to remove moisture. The resulting white fluffy solid is then transferred to a covered crucible and placed in a muffle furnace at 3 o The heating rate was increased to 550 C / min. o C for 4 h, and the obtained light yellow solid was named BCN.

[0057] Step 4: The BCN described in step 3 was placed in a nitrogen atmosphere tube furnace and calcined at 600 °C for 2 hours, with a heating rate of 3 °C / min and a N2 flow rate of ~40 mL / min. After cooling naturally to room temperature, the solid powder was collected for use without further grinding and named CN.

[0058] Step 5: The CN powder (100 mg) prepared in step 4 was uniformly dispersed in 10 mL of deionized water by ultrasonic treatment to obtain a uniform CN dispersion solution; Step 6: Add 1.27 mL of Au22Ag3 NCs described in step 2 to the solution described in step 5, stir for 1 h, and then freeze-dry to obtain the sample Au22Ag3 / CN Step 7: The Au22Ag3 / CN catalyst obtained in step 6 was tested for photocatalytic water decomposition and hydrogen production. The photocatalytic water decomposition and hydrogen production test was carried out at room temperature using a top-illuminated quartz reactor. 20 mg of the composite photocatalyst was dispersed in 20 mL of aqueous solution containing 2 mL of triethanolamine sacrificial agent, and a uniform suspension was obtained by brief sonication. Before illumination, N2 was purged for 30 min to remove dissolved O2. Then, the reactor was sealed and placed under a 300 W xenon lamp (PLS-SXE 300, Beijing Bofeilai) equipped with a UV cutoff filter (λ >420 nm) to evaluate the hydrogen evolution reaction performance under visible light, and the output light intensity was maintained at 100 mW cm−2. The gas products were sampled and analyzed by gas chromatography (Shimadzu GC-2014, equipped with a thermal conductivity detector (TCD) and a 5A molecular sieve column, with N2 as the carrier gas) at intervals of 1 h.

[0059] The Au22Ag3 / CN photocatalyst prepared according to the preparation method described in this example has a photocatalytic performance test result as shown in the figure. Figure 5 As shown in the figure, after 4 hours of reaction under visible light conditions, the hydrogen production of Au22Ag3 / CN photocatalyst reached 19.41 µmol.

[0060] like Figure 1 As shown in the figure, Au12Ag13 / CN-3 shows a nanostructure similar to CN, both of which are curled flake structures. At the same time, due to the extremely small size of Au12Ag13 NCs, their existence cannot be observed by SEM. The SEM schematic diagram of Au12Ag13 / CN-3 shows that the loading of Au12Ag13 does not destroy the unique lamellar structure of CN.

[0061] like Figure 2As shown, the TEM image of Au12Ag13 NCs shows that the clusters are monodisperse without any agglomeration. By analyzing the size distribution, it can be seen that the average particle size of the clusters is 1.2±0.4 nm.

[0062] from Figure 3 As can be seen from the TEM image, Au12Ag13 NCs are well dispersed on CN without serious aggregation. Figure 3 As shown in the histogram in the middle inset, the average particle size of the loaded Au12Ag13 NCs is about 1.5 nm. Therefore, compared with the initial size of 1.2 nm, the size of NCs has increased slightly after loading, which may be due to the weak anchoring effect between a small number of NCs and the carrier CN. However, in general, the size of most NCs is still less than 2 nm, and there is no serious agglomeration, which meets the broad definition of NCs.

[0063] like Figure 4 As shown in Figure 3, pristine CN has almost no photocatalytic activity under visible light, which may be due to the rapid recombination of photogenerated charges in pure g-C3N4, which limits the generation of hydrogen. The reactivity of the Au12Ag13 / CN composite material is greatly improved after cluster modification. The hydrogen production rate of Au12Ag13 / CN-3 is 1.24 times that of Au25 / CN, which may be related to the synergistic effect of Au and Ag.

[0064] like Figure 5 As shown in the figure, after adjusting the ratio of Au to Ag in the AuAg alloy clusters, the three photocatalysts Au22Ag3 / CN, Au18Ag7 / CN and Au12Ag13 / CN prepared all showed higher photocatalytic activity than Au25 / CN, further indicating that the synergistic effect between Au and Ag can effectively promote the photocatalytic process. Among them, Au12Ag13 / CN showed the best catalytic activity.

[0065] like Figure 6 As shown, the stability test of Au12Ag13 / CN-3 photocatalytic hydrogen production shows that the composite catalyst has good cycle stability and has the potential for large-scale application.

Claims

1. A method for preparing AuAg alloy cluster / g-C3N4 photocatalyst, characterized in that: The following steps are involved: Step 1: Add HAuCl4 aqueous solution and AgNO3 aqueous solution to MHA aqueous solution under stirring to form MHA-Au(I) / Ag(I) complex; Step 2: Add H2O, NaOH solution and NaBH4 solution in sequence, stir the mixed solution at room temperature to react and obtain reddish brown Au x Ag 25-x NCs; Step 3: Dissolve dicyandiamide and ammonium chloride in deionized water, then dry to obtain a white fluffy solid, and calcine to obtain a light yellow solid BCN; Step 4: Grind the BCN and place it in a protective atmosphere for secondary calcination to prepare a few layers of g-C3N4 through a secondary thermal stripping process, cool it naturally to room temperature, and collect the solid powder CN for later use without grinding; Step 5: Disperse CN powder evenly in deionized water; Step 6: Add Au separately x Ag 25-x NCs, stirring for reaction and then drying to obtain the AuAg alloy clusters / g-C3N4 photocatalyst.

2. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: In step 1, the concentrations of the HAuCl4 aqueous solution and the AgNO3 aqueous solution are both 20 mM, and the concentration of the MHA aqueous solution is 5 mM; the amount of the HAuCl4 aqueous solution added is 0.24 ~ 0.44 mL, the amount of the AgNO3 aqueous solution added is 0.06 ~ 0.26 mL, and the amount of the MHA aqueous solution added is 4 mL.

3. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The amount of H2O added in step 2 is 4 mL, the concentration of the NaOH aqueous solution is 1 mM, the amount added is 300 µL, the concentration of the NaBH4 solution is 20 mM, the amount added is 100 µL, and the NaBH4 solution is prepared by dissolving 43 mg NaBH4 in 10 mL of the NaOH aqueous solution.

4. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The stirring reaction time in step 2 is 3 h.

5. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The amount of dicyandiamide added in step 3 is 1 g, the amount of ammonium chloride added is 5 g, and the amount of H2O used is 10 mL; the mass of the CN powder in step 5 is 100 mg, and the amount of H2O used is 10 mL; the Au in step 6 is x Ag 25-x The amount of NCs added was 0.254-7.62 ml, and the reaction time was 1 h.

6. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The drying in step 3 and step 6 is to freeze-dry the solution in a freeze dryer.

7. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The calcination in step 3 is carried out in a muffle furnace with the following specific parameters: heating to 550° C. at a heating rate of 3° C. / min and maintaining for 4 h.

8. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The calcination in step 4 is carried out in a tubular furnace with the following specific parameters: heating to 600°C at a heating rate of 3°C / min and maintaining for 2h; the protective atmosphere is nitrogen with a nitrogen flow rate of 40 mL / min.

9. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: The dispersion in step 5 is carried out by ultrasonic treatment.

10. The method for preparing the AuAg alloy cluster / g-C3N4 photocatalyst according to claim 1, characterized in that: In step 1, HAuCl4 is 20 mM, 240 µL, and AgNO3 is 20 mM, 260 µL; in step 6, Au x Ag 25-x The amount of NCs added was 2.54 ml.

Citation Information

Patent Citations

  • Ag / g-C3N4 composite photocatalyst and preparation method thereof

    CN106975507A

  • Preparation method and application of metal nanocluster modified ultrathin 2D g-C3N4 / ZnIn2S4 heterojunction photocatalyst

    CN117358277A

  • Competitive colorimetric fluorescence dual-mode sensor of graphene-like carbon nitride-based ternary composite material, and preparation method and application thereof

    CN117825682A

  • Bimetal particle modified g-C3N4 photocatalyst as well as preparation method and application thereof in photocatalytic cellulose-based biomass reforming hydrogen production

    CN118751237A